Growth and development indicators of Sporobolus indicus (L.) R. Br. (smutgrass) in an agroecosystem of Panicum maximum cv. Likoni - Sardi?as, Yurangel; Padilla, C?sar; Herrera, Rafael Segundo; Noda, Aida; Fraga, N. (Cuban Journal of Agricultural Science, 2010)
The research was developed in the cattle unit B of the Institute of Animal Science, located at the Havana province, Cuba, on typical red ferrallitic soil. Through a sampling design, the homogeneity of the experimental area was determined corresponding to a grassland of Panicum maximum cv. Likoni with infestation of Sporobolus indicus (L.) R. Br. (wiregrass). A sample size of 43 plants was selected to choose linear and nonlinear models of best fit to the characteristics evaluated. The variables percentage of leaves and that of dead material was fitted to the quadratic model, and the number of tillers to the Gompertz, and the yield of total dry matter (DM) and dead material to the logistic model. The DM yield of wiregrass was estimated indicating that a similar proportion is not produced in Guinea grass Likoni due to the effect of competence for living space. The period from the formation of panicles to the morphological maturity of seeds comprised from the sixth to the twelfth week of regrowth, implying that the plant cycle of wiregrass was of 84 d during the dried season. These results could contribute to the determination of the right time to start the labors of soil preparation in degraded grasslands. With this information, the culmination of the reproductive cycle of wiregrass could be avoided thereby hampering the increase of the seed bank in the soil. Key words: e.